2020
DOI: 10.17485/ijst/v13i44.1479
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of Latent Semantic analysis and Latent Dirichlet allocation topic modeling methods using Bible data

Abstract: Objective: To compare the topic modeling techniques, as no free lunch theorem states that under a uniform distribution over search problems, all machine learning algorithms perform equally. Hence, here, we compare Latent Semantic Analysis (LSA) or Latent Dirichlet Allocation (LDA) to identify better performer for English bible data set which has not been studied yet. Methods: This comparative study divided into three levels: In the first level, bible data was extracted from the sources and preprocessed to remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
1
0
3
Order By: Relevance
“…The NLP pipeline focused on evaluating the most mature and best performing topic modeling algorithms reported in the literature. For example, Garbhapu and Bodapati (2020) found that LDA was better than LSA at aligning word associations with human word associations [38]. Kherwa and Bansal (2019) assessed that LDA was more efficient than other topic modeling algorithms [28].…”
Section: Latent Semantic Analysismentioning
confidence: 99%
“…The NLP pipeline focused on evaluating the most mature and best performing topic modeling algorithms reported in the literature. For example, Garbhapu and Bodapati (2020) found that LDA was better than LSA at aligning word associations with human word associations [38]. Kherwa and Bansal (2019) assessed that LDA was more efficient than other topic modeling algorithms [28].…”
Section: Latent Semantic Analysismentioning
confidence: 99%
“…Terdapat bebeberapa metode dalam topic modeling, salah satunya adalah Latent Dirichlet Allocation (LDA). LDA merupakan salah satu metode yang paling populer dalam pemodelan topik (Alghamdi & Alfalqi, 2015;Bastani et al, 2019;Garbhapu, 2020;Hidayatullah et al, 2019;Jelodar et al, 2018;Kim et al, 2022;Lyu et al, 2021;Madzík & Falát, 2022;Myat Noe Win, Sri Devi Ravana, 2022;Nurlayli & Nasichuddin, 2019;Sutherland et al, 2020;Yokomoto et al, 2012;Zoghbi et al, 2016). Gambar 1 menunjukkan alur metode penelitian pemodelan topik menggunakan LDA.…”
Section: Metode Penelitianunclassified
“…Dalam penelitian ini menggunakan metode Latent Dirichlet Allocation (LDA) untuk menganalisis tren terkait PTMT. LDA menerapkan model generative probabilistic untuk pengumpulan data diskrit sebagai korpus, sehingga didapatkan struktur semantik dan mendeteksi topik-topik yang ada pada koleksi data teks yang diproses dan proporsi kemunculan topik tersebut (Garbhapu, 2020;Nurlayli & Nasichuddin, 2019;Pinto & Chahed, 2015). Ilustrasi cara kerja LDA dapat dilihat pada Gambar 2.…”
Section: Topic Modelingunclassified
“…Model LDA menghasilkan ringkasan yang singkat, jelas, dan koheren [7]. LDA ditemukan sebagai metode komputasi yang efisien dan dapat ditafsirkan dalam mengadopsi bahasa Inggris Kumpulan data Alkitab Versi Internasional Baru yang belum dibuat daripada metode LSA [8]. Dalam sentiment analisis mengenai data twitter tentang kendaraan listrik menunjukan bahwa LDA memberikan yang lebih baik wawasan tentang topik, serta akurasi yang lebih baik daripada LSA [9].…”
Section: Jiko (Jurnal Informatika Dan Komputer)unclassified